The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/m849
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl 6-Amino-1-methyl-9H-carbazole-2,3-dicarboxylate

Abstract: Abstract:The title compound (2) was prepared in high yield by catalytic transfer hydrogenation of the 6-nitro precursor (1), using hydrazine hydrate as the hydrogen source. Under the conditions employed, the ester groups remain unaffected. The new compound was fully characterised by elemental analysis, . Such compounds are known to act as topoisomerase II poisons and as another common structural feature they possess a heteroaromatic ring fused to the carbazole 2,3-bond. Typically, this is a pyridine unit (like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…With the 2-nitro compound 4a [ 16 ] and the new 4-nitro isomer 4b in hands, preparation of the corresponding two amino-substituted Luotonin A derivatives should be feasible in a straightforward manner by reduction of the NO 2 group. While Cagir et al [ 20 ] had obtained 8-amino-Luotonin A from the 8-nitro precursor by reduction with SnCl 2 in moderate yield (40%) and Dallavalle et al [ 25 ] had reported an unsuccessful attempt to selectively reduce the nitro group in 9-nitro-Luotinin A by catalytic hydrogenation in acetic acid, we decided to apply a protocol that had been successfully used for the reduction of nitrocarbazoles into aminocarbazoles [ 26 , 27 ]. This method makes use of hydrazine hydrate as hydrogen source in a catalytic transfer hydrogenation reaction in alcoholic solution or suspension at elevated temperature.…”
Section: Resultsmentioning
confidence: 99%
“…With the 2-nitro compound 4a [ 16 ] and the new 4-nitro isomer 4b in hands, preparation of the corresponding two amino-substituted Luotonin A derivatives should be feasible in a straightforward manner by reduction of the NO 2 group. While Cagir et al [ 20 ] had obtained 8-amino-Luotonin A from the 8-nitro precursor by reduction with SnCl 2 in moderate yield (40%) and Dallavalle et al [ 25 ] had reported an unsuccessful attempt to selectively reduce the nitro group in 9-nitro-Luotinin A by catalytic hydrogenation in acetic acid, we decided to apply a protocol that had been successfully used for the reduction of nitrocarbazoles into aminocarbazoles [ 26 , 27 ]. This method makes use of hydrazine hydrate as hydrogen source in a catalytic transfer hydrogenation reaction in alcoholic solution or suspension at elevated temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Replacement of gaseous hydrogen with liquid or solid hydrogen sources in catalytic hydrogenation reactions is generally referred to as catalytic transfer hydrogenation [13] and it offers some advantages in terms of safety, as well as easier reaction monitoring and (in some cases) easier work-up. We previously made positive experiences with the selective reduction of a nitrocarbazolediester by catalytic transfer hydrogenation [14], employing Deady's protocol [15]. Recently, we successfully employed this technique also to the synthesis of A-ring amino derivatives of Luotonin A [4].…”
Section: Resultsmentioning
confidence: 99%